Mediatization and the Absence of the Environment. Issue 4 (2nd October 2020) - Kannengießer, Sigrid; McCurdy, Patrick
Abstract: Mediatization remains a key concept for theorizing how our ever-evolving and intensifying media and communications environment underwrites and (re)constructs our social world, yet the socio-ecological effects of mediatization processes remain relatively unacknowledged within this research field. However, mediatization must be conceptualized as a cogent process whose impact extends beyond the confines of the "media environment" to the natural environment. We make this argument by reviewing how three dominant traditions of mediatization scholarship: (a) institutionalist, (b) cultural/social constructivist, and (c) materialist conceptualize "the environment." We argue that scholars rarely acknowledge the materialist dimension of mediatization despite it being a fundamental aspect of mediatization processes. Consequently, we bring discourse surrounding the materiality of mediatization to the fore by drawing on theories of materiality from media and communication studies in general and highlighting three material dimensions of mediatization processes in particular: (a) resources, (b) energy, and (c) waste. In doing so, we make explicit the implicit material dimensions of mediatization processes that have been largely overlooked but are directly linked to how we understand, theorize and react to the societal, cultural, economic, environmental transformations brought about by media.